Rural School Organizational Learning Patterns and Variation - Dedi Irwan; Muhammad Iqbal Ripo Putra; Nurussaniah Nurussaniah; Nindy Debbytha Adystifanny; Magdalena Simanjuntak (STKIP Singkawang, 2023)
This paper derives from a depth study of the patterns and variations of school organizational learning (OL) application in rural schools in supporting their teachers’ professional continuous learning (PL). By using total sampling, 172 out of 211 teachers from all primary and junior secondary schools were assigned to spend two days in the survey. Our research findings indicate that teachers and school leaders put high scores on values and practices of school organizational learning. The high values given by the teachers can be translated that they believe that practicing organizational learning is important in order to support and sustain their own professional learning. an optimistic effort on improving school organizational learning. We suggest that the teachers’ needs on improving their professional learning tend to be homogeneous. It could ease the process of improving school organizational learning which could accommodate and address typical challenges and need of teachers.